Vagus Nerve Stimulation Affects Pain Perception in Depressed Adults - Jeffrey J Borckardt; F Andrew Kozel; Berry Anderson; Angela Walker; Mark S George (Pain Research and Management)
BACKGROUND: Previous research suggests that vagus nerve stimulation (VNS) affects pain perception in epilepsy patients, with acute VNS decreasing pain thresholds and chronic VNS treatment increasing pain thresholds. However, no studies have investigated the effects of VNS on pain perception in chronically depressed adults, nor have controlled, systematic investigations been published on the differential effects of certain VNS device parameters on pain perception.